Hubungan Anemia Pada Ibu Hamil Dengan Berat Badan Bayi Di RSUD Dr. H. Soewondo Kendal - Aulia Putri, Desmatika; Kartika Ishartadiati; Andra Agnez Al Aska; Sukma Sahadewa (Calvaria Medical Journal, 2024)
This research was motivated by an increase in the prevalence of anemia in pregnant women, namely according to (Riskesdas) in 2013, it was stated that the increase in the prevalence of anemia in pregnant women increased from 37.1% to 48.9%. Meanwhile, in Central Java Province, the prevalence of anemia in pregnant women is 43.5%. The impact caused by a pregnant mother suffering from anemia is that it inhibits the growth and development of the fetus in her womb. Apart from that, it can cause bleeding during the birth process, the baby is born with a low body weight, decreased intelligence, the baby's immunity decreases and the baby easily suffers from malnutrition. The research carried out had the aim of finding out the relationship between anemia in pregnant women and the weight of newborn babies at RSUD Dr. H. SOEWONDO KENDAL 2020 – 2021. Data collection uses the statistical data set method which is the use of data that is already available or called secondary data. Meanwhile, the data test uses the Spearman Rank test method. The relationship between anemia in pregnant women and the weight of newborn babies can be seen from the significance value, where the significance value in this study used the Spearman Rank test, namely 0.707 (p=0.707) where when compared with the value α=0.05 then p > 0 .05. So it shows that there is no relationship between anemia in pregnant women and the weight of newborn babies.